2012
DOI: 10.1016/j.amjsurg.2011.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Research priorities in surgical simulation for the 21st century

Abstract: Background Despite a tremendous growth research in surgical simulation remains uncoordinated and unfocused. The objective of this study was to develop research priorities for surgical simulation. Methods Using a systematic methodology (Delphi), members of the Association for Surgical Education submitted 5 research questions on surgical simulation. An expert review panel categorized and collapsed the submitted questions and redistributed them to the membership to be ranked using a priority scale from 1(lowest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 22 publications
0
38
0
Order By: Relevance
“…Simulation Committee conducted individualized narrative literature reviews for each of the ten most important research priorities identified in the prior Delphi study 4 . An expert panel then collated the results to give a comprehensive overview of the current landscape for each priority.…”
Section: Participants and Identification Of Relevant Literature: Selementioning
confidence: 99%
See 1 more Smart Citation
“…Simulation Committee conducted individualized narrative literature reviews for each of the ten most important research priorities identified in the prior Delphi study 4 . An expert panel then collated the results to give a comprehensive overview of the current landscape for each priority.…”
Section: Participants and Identification Of Relevant Literature: Selementioning
confidence: 99%
“…As a result, the progress made in the different areas of surgical simulation research is uneven and remains relatively unknown. In order to bring a degree of focus and direction to this important area of research, the Association for Surgical Education (ASE) Simulation Committee applied a systematic approach (i.e., a Delphi process) to identify the most important research priorities in surgical simulation 4 . With this article, the ASE Simulation Committee aims to report on the progress made since the turn of the century in each research priority for surgical simulation and to identify prime areas for ongoing research.…”
Section: Introductionmentioning
confidence: 99%
“…An established precedent exists from other surgical specialties such as the Fundamentals of Laparoscopic Skills and ACS/APDS Surgical Skills Curriculum, which are both used successfully for credentialing and certification of surgeons. [27][28][29] The authors are not alone in thinking that it would be beneficial to have a standardized laparoscopic skills certification for graduating residents. 3,17 Competency-based education is under development through the ACGME Milestones initiative and the Royal College CanMEDS (Canadian Medical Education Directions for Specialists) 2015.…”
Section: Moving Forward Collaborativelymentioning
confidence: 99%
“…Stefanidis et al (2012) state that the future research agenda and priority research questions for simulated surgery needs to define coordinated efforts and clarify common goal and direction [95]. Studies are required to present evidence validating whether or not simulators can improve patient outcomes, transfer to improved clinical performance and competence, leading to increased patient safety.…”
Section: 6mentioning
confidence: 99%